Phase 1, open-label, dose-escalation study of sorafenib in combination with eribulin in patients with advanced, metastatic, or refractory solid tumors - Marmé, Frederik (Cancer chemotherapy and pharmacology, 2018)
Combining sorafenib and eribulin mesylate may provide synergistic antitumor activities with limited overlapping toxicities. This phase 1b, open-label, dose-escalation study evaluated safety, pharmacokinetics, maximum tolerated dose/recommended phase 2 dose (MTD/RP2D), and preliminary efficacy of sorafenib plus standard-dose eribulin mesylate in patients with advanced, metastatic, or refractory tumors. Patients received sorafenib 200 mg twice daily (BID; n = 5), 600 mg/day (n = 8), and 400 mg BID (MTD; n = 27). Dose-limiting toxicities were increased alanine aminotransferase and acute coronary syndrome (both grade 3) in the 400-mg BID dose-escalation and expansion cohorts, respectively. No significant increase in mean QTcF duration was observed with eribulin plus sorafenib versus eribulin alone; there were no drug-drug interactions. Five patients achieved partial response; 16 achieved stable disease. The combination of sorafenib and eribulin mesylate presented no unexpected safety concerns and no significant impact on QT/QTc intervals or drug-drug interactions. Sorafenib 400 mg BID plus standard-dose eribulin is the RP2D.